The Role of Hotel Public Relations in Crisis Management During The Covid-19 Pandemic - Muhammad Edy Susilo; Prayudi Prayudi (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2022)
The hotel industry has felt the impact of the COVID-19 pandemic. The social restriction policy implemented by the government to prevent the transmission of the virus has made mobility levels decline, and hotel occupancy rates have drastically decreased. This pandemic has created severe crisis management. This research was conducted at two five-star hotels in Yogyakarta to determine how public relations practices deal with crisis management. One hotel is a local brand, and the other is included in an international hotel chain. The novelty of this research is in the nature of the crisis, which does not have a pre-crisis stage. The research was conducted with qualitative research methods and using a subjective approach. The data was dug in depth from hotel management, employees, and customers. When the research was conducted, the crisis had not yet ended, so the researcher focused on efforts to overcome the crisis and had not yet arrived at the post-crisis condition. The results showed that there was a shock from the management over the impact of the pandemic. Therefore, these two hotels need time to overcome the crisis in different timescales. Further, the leadership began to take the necessary strategic steps: forming a crisis management team, working with professional consultants (for international chain hotels), preparing crisis management plans, identifying laws or government regulations regarding Covid-19, and taking action. At the same time, marketing and public relations are spearheading in improving marketing and maintaining the brand during times of crisis. However, the hotel is still faced with the aspect of occupancy amid low supply. Meanwhile, public relations maintain a brand image as a form of investment that can be reaped when the crisis is over.